Magda Nachman : an artist in exile - Bernstein, Lina, 1949- (Modern biographies., 2020)
"The political and social turmoil of the twentieth century took Magda Nachman from a privileged childhood in St. Petersburg at the close of the nineteenth century, artistic studies with Léon Bakst and Kuzma Petrov-Vodkin at the Zvantseva Art Academy, and participation in the dynamic symbolist/modernist artistic ferment in pre-Revolutionary Russia to a refugee existence in the Russian countryside during the Russian Civil War followed by marriage to a prominent Indian nationalist, then with her husband to the hardships of émigré Berlin in the 1920s and 1930s, and finally to Bombay, where she established herself as an important artist and a mentor to a new generation of modern Indian artists"--